Associação entre aspectos clínicos, nutricionais, sociocomportamentais e perfil cronotipo em adultos assistidos pela Estratégia Saúde da Família (ESF) - Canaan, Juliana Cristina dos Reis (2021)
Chronotype (CT) represents the phenotypic expression of an individual's circadian rhythms, reflecting the preference for specific behavior patterns at certain times of the day (morning, afternoon or evening). CT has been associated with a greater predisposition to the occurrence of chronic non-communicable diseases (NCDs), such as obesity, diabetes mellitus and cardiovascular diseases. Due to the high prevalence, repercussions and high cost involved, these diseases represent important public health challenges. NCDs have high morbidity and mortality, especially in middle and low-income populations, which are the main users of the Family Health Strategy (ESF) in Brazil. The effects of the CT on users of the public health system are still poorly explored. In this sense, the identification of circadian and behavioral risk patterns can assist in the multidisciplinary planning and execution of preventive and health promotion measures for the Unified Health System (SUS). Thus, the aim of this study was to evaluate the relationship between clinical, socio-behavioral and nutritional aspects with CT in adults assisted by the FHS. This is a population-based cross-sectional study. The sample consisted of 380 individuals, selected by means of probabilistic sampling by clusters in a proportional and systematic way in a municipality of approximately 100 thousand inhabitants, located in the south of Minas Gerais. Data collection was performed during home visits, in which general and nutritional anamnesis, measurement of anthropometric measures and application of the Food Frequency Questionnaire, followed by the Morningness-Eveningness Questionnaire (MEQ) to determine the CT were carried out. The data were analyzed using the Chi-square test, Principal Component Analysis (CPA) and Fisher's Discriminant Analysis to determine the clinical, socio-behavioral and nutritional aspects associated with each CT (morning, evening or intermediate). The morning group was characterized by older men, with less than eight years of schooling, with low body mass index (BMI) and with low intake of omega-6 and omega-3, sodium, zinc, thiamine, pyridoxine and niacin. The evening group, on the other hand, was composed of younger individuals, with high BMI, with a high consumption of these same nutrients and a higher frequency of heart diseases (p < 0.05). It was concluded that most morning CT individuals were older men, with lower BMI and lower consumption of omega-6 and -3, sodium, zinc, thiamine, pyridoxine and niacin, whereas evening individuals were younger, had higher BMI and had higher consumption of the studied micronutrients. The identification of circadian and behavioral risk groups can help to provide preventive and multidisciplinary health promotion measures.